(untitled) (The Journal of Plant Protection Sciences, 2024)
In India, brinjal is the 4th most important vegetable grown after potato, onion and to mato. According to an estimate about 1.4 mil lion small and marginal farmers in India grow brinjal crop, which provide regular and steady income to them (2). West Bengal has the lion share in brinjal production (29.1%) in India, occupying the highest in acreage and produc tion of brinjal among the states. A major group of farmers are involved in brinjal culti vation for their income generation throughout West Bengal. Presently cultivated area of brinjal in West Bengal is 158.44 thousand ha with a production and productivity of 2870.60 thousand tones and 18.11 ton/ha (Economic Review, 2010-11, Govt. of West Bengal). Wilting or death of brinjal plant is the major constraint in brinjal cultivation.